Sex-Biased Habitat Use by Phyllostomid Bats on Riparian Corridors in a Human Dominated Tropical Landscape - de la Peña-Cuéllar, Erika; Benítez-Malvido, Julieta (Frontiers in Ecology and Evolution, 2021)
Some animal species exhibit sex-specific patterns as an adaptation to their habitats however, adaptability to a human-dominated landscape is commonly explored without considering intraspecific sexual differences. Differences between males and females lead to a sexual segregation in habitat use. In southern Mexico, we explored sex-specific responses to landscape modification of six common species of phyllostomid bats: Artibeus jamaicensis, A. lituratus, Sturnira lilium, Carollia perspicillata, Glossophaga soricina and Platyrrhinus helleri using riparian corridors within continuous forest and cattle pastures. Furthermore, we explored sex related responses to vegetation attributes (i.e., tree height and basal area) and seasonality (i.e., wet and dry seasons). Overall, capture rates were significantly skewed towards females and riparian corridors in pastures. Females of A. lituratus and G. soricina exhibited a strong positive relationship with greater tree height and basal area. Seasonality was important for A. lituratus and S. lilium females, only. The results indicate a sexual driven response of bats to habitat modification. The high energetic demands of females associated to reproduction could lead to foraging into riparian corridors in pastures. The presence of large trees along riparian corridors in pastures may help maintaining a diverse and dynamic bat community in modified tropical landscapes.